(untitled) (Journal of the Spanish Institute for Strategic Studies, 2025)
The following paper aims to analyze the main events that have occurred in Ethiopia from the time Prime Minister Abiy Ahmed came to power in April 2018 until September 2024. During the first months of his tenure, his public image saw a meteoric rise, culminating in the award of the Nobel Peace Prize in 2019, only to become highly unpopular in the country shortly thereafter, particularly among the Oromo and Tigrayan communities. Here, we will outline the successes of his policies, encapsulated in his Medemer ideology, as well as his failures, especially those related to the Tigray war, the Oromo issue, the Amhara Fano insurgency, and the recent crisis triggered by Ethiopia’s access to a Red Sea port.